Role and Mechanism of Olfactory Stem Cells in the Treatment of Olfactory Disorders - Shengqi Gan; Siyuan Qu; Hai Zhu; Mengdan Gong; Yizhen Xiang; Dong Ye (Stem Cells International)
Olfactory dysfunction is one of the most prevalent diseases in otorhinolaryngology, particularly since the coronavirus 2019 (COVID-19) pandemic, with a potential impact on daily life. Several etiological factors can contribute to olfactory dysfunction owing to the complexity and specificity of the olfactory transmission pathway. However, current treatments for olfactory dysfunction are limited and their efficacy is unsatisfactory. Olfactory stem cells are multifunctional stem cells in the olfactory mucosa that comprise both horizontal and global basal stem cells (HBCs and GBCs, respectively). These cells can differentiate into various cell types in response to different stimuli with distinct characteristics. The aim of the study was to discuss the mechanisms and functions of stem cells and their application in the treatment of olfactory dysfunction.